PROFIL SUBAK DI DAERAH PERKOTAAN (STUDI KASUS SUBAK BUAJI KELURAHAN KESIMAN KECAMATAN DENPASAR TIMUR) - Made Sujana; Made Tamba; Made Sukerta (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The purpose of this research is to know the profile of Subak Buaji and to identify the inhibiting factors in maintaining the continuity of Subak Buaji, Kesiman Sub-District, East Denpasar District. The selection of research sites conducted intentionally and the determination of respondents conducted by the method of quota sampling with the number of respondents who set 30 people. The result of the discussion of Subak Buaji Profile is the only subak in Kelurahan Kesiman Denpasar Timur with the number of 147 members, with 140 farming area and the production of rice plant in Subak Buaji reaches 100,28 ton in one harvest season, subak Buaji divided into four farmer group among others Munduk Padang Gambu, Munduk Pak Sale, and Munduk Buaji. The inhibiting factors in maintaining the continuity of Subak Buaji are technical aspects related to inhibiting factors, namely lack of irrigation water supply and the rampant transfer of land function in Subak Buaji and lack of administrative or cooperative members of subak to ease the burden of farmers to grow crops. Suggested Concept Tri Hita Karana in Subak Buaji must continue to run and in make the guidelines for the farmers, make the farmers aware of the importance of water for life that should be on guard and preserved so that Subak Buaji survival remains steady. Establish different cropping patterns each year such as rice crops or rice crops, to overcome the shortage of water availability that occurs throughout the year in Subak Buaji.